Exosomal miR-122 derived from M2 macrophages induces osteogenic differentiation of bone marrow mesenchymal stem cells in the treatment of alcoholic osteonecrosis of the femoral head - Guoping Le; Riyou Wen; Huaixi Fang; Zhifa Huang; Yong Wang; Hanwen Luo (Journal of Orthopaedic Surgery and Research)
Abstract Alcoholic osteonecrosis of the femoral head (AIONFH) is caused by long-term heavy drinking, which leads to abnormal alcohol and lipid metabolism, resulting in femoral head tissue damage, and then pathological necrosis of femoral head tissue. If not treated in time in clinical practice, it will seriously affect the quality of life of patients and even require hip replacement to treat alcoholic femoral head necrosis. This study will confirm whether M2 macrophage exosome (M2-Exo) miR-122 mediates alcohol-induced BMSCs osteogenic differentiation, ultimately leading to the inhibition of femoral head necrosis. M2 macrophages were identified by flow cytometry, and the isolated exosomes were characterized by transmission electron microscopy (TEM) and Nanoparticle Tracking Analysis (NTA). Next, miR-122 was overexpressed by transfecting miR-122 mimic, and the expression of miR-122 in M2 macrophages and their exosomes was evaluated. Subsequently, the effect of exosomal miR-122 on the osteogenic differentiation ability of BMSCs was detected, including cell proliferation, expression of osteogenic-related genes (RUNX2, BMP2, OPN, ALP), and calcium nodule formation. Finally, the therapeutic effect of M2-Exo was analyzed in a rat model of AIONFH, and bone repair and pathological damage were evaluated by Micro-CT, RT-qPCR, HE, Masson staining, and immunohistochemistry (COL I). The results showed that M2 macrophages were successfully polarized, with an average M2-Exo particle size of 156.4 nm and a concentration of 3.2E + 12 particles/mL. The expression of miR-122 in M2 macrophages is significantly higher than that in M0 macrophages, and miR-122 mimic can increase the content of miR-122 in M2-Exo. miR-122 in M2-Exo can promote osteogenic differentiation of rat bone marrow BMSCs, enhance cell viability, and increase the expression of osteogenesis-related genes. After being applied to the AIONFH rat model, the injection of M2-exo and miR-122 mimics significantly improved the repair effect of articular cartilage, alleviated pathological changes, and promoted the regeneration of bone tissue. M2-macrophage-derived exosomal miR-122 induces osteogenic differentiation of bone mesenchymal stem cells in treating AIONFH.